Autogenous Vein Wrapping versus In Situ Decompression for Management of Secondary Cubital Tunnel Syndrome after Surgical Fixation of Elbow Fractures: Short-Term Functional and Neurophysiological Outcome - Sadek, Ahmed F.; Fouly, Ezzat H.; Abdel-Aziz, Adel A.; Sayed, Mohammed A.; EL-Mahboub, Nehad M.; Hamdy, Mona (Journal of Hand and Microsurgery, 2016)
Purpose The aim of this study was to compare the functional and neurophysiological outcome of in situ decompression versus in situ decompression augmented with autogenous vein wrapping in management of secondary cubital tunnel syndrome at the elbow following fixation of elbow fractures.Methods A prospective comparative randomized study was performed on 29 patients who were divided into two groups: group I (in situ decompression) and group II (in situ decompression augmented with autogenous vein wrapping). We measured the patients' demographics, subjective reports of symptoms, and objective evaluation of the functional and neurophysiological outcomes of both groups.Results Group II patients achieved statistically better results in both neurophysiological scoring and clinical sensory rating but not in all other parameters.Conclusion Autogenous vein wrapping for secondary cubital tunnel syndrome after elbow fracture fixation only provides a better sensory outcome.Level of Evidence Level II, therapeutic prospective comparative study.
Keywords: vein wrapping; in situ decompression; secondary cubital tunnel syndrome; elbow fractures